2015
DOI: 10.4317/medoral.20491
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of level IIb neck dissection in oral squamous cell carcinoma

Abstract: BackgroundThe purpose of this study was to determine the prevalence of level IIb metastasis in patients with oral squamous cell carcinomas (OSCCs).Material and MethodsA prospective analysis of 56 patients with OSCC who underwent surgical treatment of the primary lesion with simultaneous neck dissection was performed. During neck dissection, level IIb lymph nodes were separately removed and processed. Neck dissection was bilateral in 26 patients (46%) and unilateral in 30 patients (54%).ResultsThe mean number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…17 Of the 208 necks taken up for surgery irrespective of clinical N stage, the overall incidence of level IIb positivity pathologically was 22 (10.5%) as 22 patient out of 182 patients (12%) revealed metastases at level IIB (p=0.001) , which was comparable with study by Dabholkar et al 18 who gave an incidence of level IIB metastases as 10.44% and Maher et al 19 in their study had level IIB incidence of 14.5%. However, de Vicente JC et al 1 found metastasis to Level IIB as 1.8%. Pugazhendi et al 20 found that Level II was the most involved site (63.3%) in the patients with SCC of the oral cavity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…17 Of the 208 necks taken up for surgery irrespective of clinical N stage, the overall incidence of level IIb positivity pathologically was 22 (10.5%) as 22 patient out of 182 patients (12%) revealed metastases at level IIB (p=0.001) , which was comparable with study by Dabholkar et al 18 who gave an incidence of level IIB metastases as 10.44% and Maher et al 19 in their study had level IIB incidence of 14.5%. However, de Vicente JC et al 1 found metastasis to Level IIB as 1.8%. Pugazhendi et al 20 found that Level II was the most involved site (63.3%) in the patients with SCC of the oral cavity.…”
Section: Discussionmentioning
confidence: 93%
“…Oral squamous cell carcinoma (OSCC) is a life-threatening disease which accounts for a burden of 32-40% of all the head and neck cancers (HNC). 1 In the Asian sub-continent oral cancer is the most common malignant tumor accounting for about one-third of all malignancies within the subcontinent and it accounts for approximately 30-40% of all cancers in India. 2 The high incidence of oral cancer and oral potentially malignant disorders in India has been linked with the habit of betel nut and tobacco chewing which is a major cause of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Six articles [ 19 , 29 , 31 , 34 , 38 , 48 ] illustrated the characteristics of cervical skip metastasis patients, which gave details of sites, T stages, isolated IIb metastases [ 45 ], and associated metastatic lymph nodes. The incidence for skip metastasis to level IV or V was low, reaching up to 8.5% [ 29 , 31 , 34 , 48 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, not all the information was complete for each study. The most common primary site for level IIb metastases was the tongue [ 22 - 24 , 45 , 47 ], reported between 2% and 28% [ 23 , 47 ]. The rate of skip metastasis among cN0 was also low, reaching 1.8% [ 19 , 29 , 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…This will invariably result in traction injury of the accessory nerve, and a subsequent neuropraxia resulting in shoulder dysfunction for very little oncological benefit in laryngeal cancer (although slightly higher metastatic rates of 3.4% are reported in the case of SCCs of the oral. 42 There also remains a consensus in addressing level IV in oral SCCs due to the presence of skip lesions, in tongue base tumors, 43 with reported rates of 2%. 44 Elective neck irradiation is as effective as elective neck dissection in the control of subclinical disease, with reported rates of 90%.…”
Section: Ijhnsmentioning
confidence: 99%